#BlackLivesMatter: black celebrity hashtag activism and the discursive formation of a social movement. Issue 3 (3rd July 2018) - Duvall, Spring-Serenity; Heckemeyer, Nicole
ABSTRACT: The #BlackLivesMatter, or #BLM, movement was founded in 2012 by Opal Tometi, Patrisse Cullors, and Alicia Garza after George Zimmerman was acquitted for the murder of Trayvon Martin. The hashtag was first used on the social media platform Twitter to call attention to the injustice of the situation. Many celebrities have taken up the hashtag and used their own social media accounts to draw attention to the movement. This is different from past forms of celebrity activism in that it seeks to change power structures within society. William Howell and Trevor Parry-Giles have demonstrated how celebrity activists have the power to destabilise police authority. Their power as celebrities translates to a perceived authority of their own with an ability to reach large audiences. In this article, we use qualitative textual analysis to identify dominant themes in black celebrity tweets about #BLM and racial justice issues. We analyse how black celebrities use Twitter to promote #BLM and what impact they have in promoting and defining the #BlackLivesMatter movement. By analysing the Twitter feeds of celebrities such as Jesse Williams, Spike Lee, Janelle Monáe, and others, this article attempts to distinguish the qualitative impact of celebrity involvement in #BlackLivesMatter.